Penerapan Problem Based Learning untuk Meningkatkan Keaktifan Siswa Kelas XI TBKR 2 SMKN 1 Selong - Agil Syahrial Haliq; M. Ismail; Bagdawansyah Alqadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this research is to find out how to increase student activity through the application of the learning model.Problem Based Learning on the Pancasila Education subject in class XI TBKR 2 SMKN 1 Selong. This study used Classroom Action Research. Data collection techniques used were interviews, observation, and documentation. Data analysis techniques used were Qualitative and Quantitative Approaches. This research was conducted in two cycles and through the application of the modelProblem Based Learningto achieve the desired success target. The results of this study indicate that in Cycle I the implementation of learning showed a figure of 66.6% then increased in Cycle II to 88.8%. Meanwhile, student activity in Cycle I reached 50% then increased in Cycle II to 87.5%. With these results, it can be said that the Classroom Action Research conducted successfully met the success indicator of 80%.